Evaluasi Efektivitas Sosialisasi dan Penegakan Hukum dalam Meningkatkan Kepatuhan Angkutan Penumpang dan Barang di Provinsi Sulawesi Tenggara - Syaiful Syaiful; Ringo Taufan Laode; Maudhy Satyadharma; Hado Hado; Mahdar Mahdar; Galih Adi Sulistyo (IRA Jurnal Pengabdian Kepada Masyarakat (IRAJPKM), 2025)
This activity aims to evaluate the effectiveness of supervision and law enforcement in passenger and freight transportation in Southeast Sulawesi Province in 2023, particularly following the GAKUM activity centered in Baubau City. The methods used included cross-agency coordination, evaluation meetings, analysis of field findings, and the formulation of joint recommendations. The evaluation meeting was held in Kendari City on December 14, 2023. The meeting was attended by 40 people. The analysis method included compiling field data and a post-meeting evaluation questionnaire. The evaluation results indicated that various violations persist, including the use of black plates, infrequent periodic inspections, and weak compliance with transportation permits. Limited task division, technical coordination, and a lack of outreach were also major obstacles. However, the evaluation activity succeeded in increasing participants' understanding and led to a more structured improvement strategy. In conclusion, inter-agency collaboration and regular evaluation are necessary to strengthen safe, orderly, and sustainable transportation governance.